2019
DOI: 10.1002/acr2.1002
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity Moderates the Association Between Psychosocial Resilience and Movement‐Evoked Pain in Knee Osteoarthritis

Abstract: ObjectiveRacial/ethnic disparities in pain are well‐recognized, with non‐Hispanic blacks (NHBs) experiencing greater pain severity and pain‐related disability than non‐Hispanic whites (NHWs). Although numerous risk factors are posited as contributors to these disparities, there is limited research addressing how resilience differentially influences pain and functioning across race/ethnicity. Therefore, this study examined associations between measures of psychosocial resilience, clinical pain, and functional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 53 publications
(74 reference statements)
3
32
0
Order By: Relevance
“…Consistent with previous findings, 3 , 44 we found that NHBs reported greater movement-evoked pain compared to NHWs; however, these differences were attenuated after controlling for clinical and sociodemographic characteristics (See Table 3 ). The causes underlying race differences in pain outcomes are complex, and the mechanisms operating on the relationship between sociodemographic factors, cultural experiences, and race are less clear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous findings, 3 , 44 we found that NHBs reported greater movement-evoked pain compared to NHWs; however, these differences were attenuated after controlling for clinical and sociodemographic characteristics (See Table 3 ). The causes underlying race differences in pain outcomes are complex, and the mechanisms operating on the relationship between sociodemographic factors, cultural experiences, and race are less clear.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, emerging research from our group suggests that among older adults with knee osteoarthritis, higher optimism and positive well-being are protective against movement-evoked pain (ie, pain-induced upon movement) in NHBs, whereas positive affect is associated with lower movement-evoked pain in NHWs. 3 These findings underscore the importance of identifying sources of resilience and their influence on pain and functioning across racial groups. Understanding these differences may facilitate the development of more culturally sensitive interventions that reduce racial disparities in pain and improve well-being among older adults.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the small sample limited our ability to examine several factors, including relevant physiological/biological markers (e.g., inflammatory cytokines) (Khan et al, 2017), or demographic characteristics such as sex and race/ethnicity. Moreover, there is a need to replicate these findings in a more diverse sample, especially given growing evidence of the impact of race/ethnicity on resilience and pain-related outcomes (Bartley et al, 2019a). Inclusion of these and other diversity variables will be important considerations for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…While factors such as anxiety and depression may increase risk for pain vulnerability, psychosocial facets such as optimism, self-e cacy, gratitude, and positive emotions are known to promote greater pain-related resilience and improve quality of life (11)(12)(13)(14). Extant research (15)(16)(17)(18) signi es that resilience (and its underlying facets) is associated with attenuated experimental pain sensitivity (19); lower pain severity, disability, and mobility impairment (16,18,20); and higher psychological functioning (21). Despite this, limited published research has examined resilience in older adults with pain.…”
mentioning
confidence: 99%